2016
DOI: 10.1177/0218492316675244
|View full text |Cite
|
Sign up to set email alerts
|

Freestyle stentless bioprosthesis for aortic valve therapy: 17-year clinical results

Abstract: Long-term results after aortic valve replacement with stentless biological prostheses compare favorably with those obtained with stented bioprostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…30 The rationale of using the stentless biological material in valve replacement surgery are the excellent hemodynamic profile, low risk of thromboembolism, and low risk of prosthetic valve infection due to the absence of artificial material. 31,32 Böning et al furthermore reported that conventional reoperation for stentless porcine xenograft root replacement could be performed with the same intraoperative results, though the 30-day mortality was worse in the xenograft group, explained by a higher amount of concomitant procedures. 33 Carefully considering patient individual CT morphological conditions, especially for nonstented valves, the option to implant transcatheter valves in case of biological valve degeneration as valve in valve procedure is a challenging but upcoming trend for reoperation in the future, especially in the older patient population with high risk of reoperation.…”
Section: Discussionmentioning
confidence: 95%
“…30 The rationale of using the stentless biological material in valve replacement surgery are the excellent hemodynamic profile, low risk of thromboembolism, and low risk of prosthetic valve infection due to the absence of artificial material. 31,32 Böning et al furthermore reported that conventional reoperation for stentless porcine xenograft root replacement could be performed with the same intraoperative results, though the 30-day mortality was worse in the xenograft group, explained by a higher amount of concomitant procedures. 33 Carefully considering patient individual CT morphological conditions, especially for nonstented valves, the option to implant transcatheter valves in case of biological valve degeneration as valve in valve procedure is a challenging but upcoming trend for reoperation in the future, especially in the older patient population with high risk of reoperation.…”
Section: Discussionmentioning
confidence: 95%
“…In both cohorts, despite different indications for operation, the in-hospital mortality and the survival do not differ signi cantly, also taking into account that concomitant procedures were carried out more often in the non-OA group. As there are 3 patients at risk after 10 years in the non-OA group, we would like to concentrate on the survival at 1 and 5 years which is compareable with current literature including different pathologies and is not showing a signi cant difference between both groups [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The favorable hemodynamic properties with a low thrombogenicity, acceptable durability and reduced transvalvular gradients demonstrate an advantage of the Freestyle® prosthesis [27]. The degeneration rate in literature reviewing long-term outcomes including a follow-up over more than 10 years shows a rate of 6.2-7.9% and a linearized detoriation rate 0.2% /100 patient years [14,15].…”
Section: Valve Degeneration and Gradientsmentioning
confidence: 99%
“…After initial excellent results, both the prostheses were withdrawn from the market, mainly due to the premature structural deterioration and the high risk of related reoperation 8,9 . Another stentless porcine aortic root, the Medtronic Freestyle aortic root (Medtronic Inc Minneapolis, MN), manufactured with an original anticalcification treatment, is still widely used for aortic root replacement with excellent long‐term results 10,11 . The Shelhigh bio‐conduit NR‐2000 (Shelhigh Inc, Milburn, NY,) as previously described, was a true, ready to use full‐biological stentless conduit.…”
Section: Discussionmentioning
confidence: 99%